Exploring urban garden ponds: considering chemical pollution as a limiting factor for insect diversity in cities - Johanna Bock; Marie Neske; Martin Krauss; Andrea Dombrowski; Jörg Oehlmann (Environmental Sciences Europe)
Abstract Background Insects are experiencing a drastic biodiversity and biomass decline while providing important ecosystem functions. Therefore, it is of great concern to further uncover underlying causes, with the goal of identifying mechanisms to dampen biodiversity loss. In urban areas, private gardens display a relevant fraction of the total green area distributed across the city. Hence, gardens pose important habitats for organisms, also as stepping stones enhancing connectivity. However, individual practices such as the use of pesticides and fertilizers, as well as chemical run-off from building materials, can strongly influence the habitat quality and thus insect biodiversity. Small water bodies, which provide important resources for many insect species, are the focus of this study. Garden pond toxicity was examined with in vitro and in vivo methods on different test organisms as well as with a chemical screening analysis. Results Out of 17 ponds, only one water sample and one sediment sample were identified as non-toxic according to a bioluminescence assay performed with Aliivibrio fischeri. In seven water and ten sediment samples, enhanced dioxin-like activity was measured with a reporter gene assay with Saccharomyces cerevisiae. The majority of water extracts displayed a mutagenic potential determined with the Ames fluctuation assay (Salmonella typhimurium, YG1041 and YG1042 strains), while most sediment extracts were not mutagenic. An increased larval mortality of Chironomus riparius was observed in five water–sediment systems implemented from pond samples. Larval mortality correlated positively with in vitro water toxicity (bioluminescence inhibition) as well as with the concentration of benzothiazole derivatives, measured in a target screening with LC–HRMS. Likely, the increased benzothiazole derivative concentrations stemmed from the installation of ethylene propylene diene monomer (EPDM) rubber pond liner. Substance composition varied significantly between house and allotment gardens and measured substance concentrations were higher in allotment ponds. Conclusions This study demonstrates that chemical pollution in private urban gardens might have been underestimated to date. Toxicity of ponds can have severe influences on insect populations and should, therefore, be studied further. The choice of materials and maintenance habits of gardeners can have a great impact on habitat qualities for insects and should not be ignored.